2020
DOI: 10.3758/s13423-019-01675-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for different types of errors being associated with different types of post-error changes

Abstract: Errors in simple choice tasks result in systematic changes in the response time and accuracy of subsequent trials. We propose that there are at least two different causes of choice errorsresponse speed and evidence quality, which result in different types of post-error changes. We explore these differences in types of errors and post-error changes in two recognition memory experiments with speed versus accuracy emphasis conditions that differentially produce response-speed and evidence-quality errors. Under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…Our findings are also in line with findings of post-error speeding in difficult tasks (Damaso, Williams & Heathcote, 2020;Williams, Heathcote, Nesbitt & Eidels, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also in line with findings of post-error speeding in difficult tasks (Damaso, Williams & Heathcote, 2020;Williams, Heathcote, Nesbitt & Eidels, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are aligned with those of Dyson and colleagues (Dyson, Sundvall, Forder & Douglas, 2018) who found that participants only slowed down after a loss when getting more cautious led to better performance, for example when they could successfully apply a strategy to guide their choice. However, when slowing down does not lead to performance improvement, participants seem not to slow down but even speed up (for similar findings see Damaso et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…We also note that for the present study, participants were instructed to weigh the speed and accuracy of their response equally and were not provided any instruction regarding whether they should (or should not) correct their errors. A recent study by Damaso et al., (2020) illustrated that when errors are committed during trials in which accuracy is prioritized over speed, performance on that trial would benefit from spending more time evaluating the incoming information and would consequently lead to post‐error slowing. However, during trials in which accuracy and response time are equally prioritized, performance on that trial would not benefit from additional information and would consequently lead to post‐error speeding.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the work of Laming (1968) and Ratcliff (1978), Ratcliff and Rouder (1998) pointed out that this pattern could be accommodated by Gaussian across-trial variability in the rate of accumulation, with mean v and standard deviation s v , and uniformly distributed across-trial variability in the starting point, with mean z and range s z . Rate variability causes slow "stimulus-quality" errors that cannot be entirely eliminated by increasing a, and starting-point variability causes fast "response-caution" errors that can be eliminated by increasing a (see Damaso et al, 2020, for further discussion of these two types of errors in evidence-accumulation models).…”
Section: Bayesian Hierarchical Ddmsmentioning
confidence: 99%